2017
DOI: 10.21109/kesmas.v11i4.1279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multilevel Intervention in Workplace Health Promotion on Workers’ Metabolic Syndrome Components

Abstract: Approximately 10-30% of adult Asian people had metabolic syndrome. This study aimed to reveal effects of workplace health promotion (WHP) with multilevel interventions on workers' metabolic syndrome component. This study was conducted in 2014-2015 using quasi-experimental design with multilevel subject intervention in Indonesia. The WHP program for multilevel intervention group included 12 weeks of combined physical training, diet, health education, social support, and advocacy. The WHP program for control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…A multilevel intervention was carried out consisting of health education lectures, printed materials and social support for workers, personal counseling for the employees’ families, advocacy for company leaders, and collaborative learning for all participants. The effects of these Working Health Promotion activities were compared with a control, in which workers received health education lectures only [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A multilevel intervention was carried out consisting of health education lectures, printed materials and social support for workers, personal counseling for the employees’ families, advocacy for company leaders, and collaborative learning for all participants. The effects of these Working Health Promotion activities were compared with a control, in which workers received health education lectures only [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The number of studies reporting each component of MetS and their proportions which recorded significant improvements compared to either baseline or control is shown in Fig 3 . Briefly, all studies that reported waist circumference found significant improvement at post-intervention [ 27 , 30 , 32 , 33 , 36 , 37 , 39 , 40 ]. More than 80% of studies found significant improvement in blood pressure [ 27 , 30 33 , 36 , 37 , 39 , 40 ], followed by 64% of studies that reported fasting blood glucose [ 30 32 , 36 , 37 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that multilevel Health Promotion at Work interventions improve dietary intake by increasing the amount of dietary fiber and reducing cholesterol intake, as well as increasing physical activity. These interventions are effective in controlling metabolic syndrome in the workplace (28).…”
Section: Discussionmentioning
confidence: 99%